Analisis Kontribusi Pariwisata Nimo Highland dan Industri Teh Malabar dalam Menggerakkan Perekonomian Lokal di Kawasan Pangalengan - Muhammad Walid Jabar; Nayla Nur Rahma; Firyal Azhar Salsabilla; Raihan Agung Permana; Mohammad Syamba’da; Nazwa Husna (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study analyzes the contribution of Nimo Highland tourism and the Malabar Tea industry in driving the local economy of the Pangalengan area. The research employs a descriptive qualitative approach by collecting data through in-depth interviews, field observations, and document analysis. Key informants include representatives from Nimo Highland management and the Malabar Tea plantation, complemented by direct observation of economic activities in both sectors. The findings indicate that Nimo Highland tourism generates short-term economic dynamics through increased visitor spending, job creation in service sectors, and the growth of local micro and small enterprises. In contrast, the Malabar Tea industry provides long-term economic stability through continuous production, employment absorption, and the maintenance of agricultural value chains. The interaction between these sectors creates a complementary relationship that strengthens local economic resilience.